Peripheral Arterial Disease: State of the Art - Vinall, Maria (MD Conference Express, 2011)
Peripheral artery disease (PAD) symptom severity is best described as a functional problem (walking speed and distance, oxygen consumption, level of physical activity, and quality of life). This article discusses claudication therapy, critical limb ischemia, revascularization strategies, treatment options for PAD, and a cost analysis of this disease.